True deep femoral artery aneurysms: Case series and review of the literature - Hiroyoshi Komai, MD, PhD; Nobuko Yamamoto, MD, PhD; Prem C. Gupta, MBBS, MS; Palma M. Shaw, MD, FACS, RPVI (JVS-Vascular Insights)
True deep femoral artery (DFA) aneurysm is a rare disease for which treatment strategies and surgical indications have not yet been precisely determined. Symptoms of true DFA aneurysms often include a pulsatile mass and tenderness in the thigh, but may be asymptomatic and incidentally diagnosed by computed tomography scan. True aneurysms are extremely rare, making up approximately 0.5% of peripheral arterial aneurysms. They are often found in elderly men and are associated with aneurysms in other areas. Indications for surgery for DFA aneurysm have not yet been determined. Whenever possible, it is important to reconstruct the DFA, because this serves as an important collateral source in case there is future development of atherosclerotic occlusive disease of the lower limb. When simple ligation of a DFA aneurysm is performed, ligation of feeding branches is important to avoid perfusion and expansion. We present a case series and review of the literature of this rare pathology.